Crosslinguistic Influence (CLI) of Lexical Breadth and Depth in the Vocabulary of Bilingual Kindergarten Children – A Bilingual Intervention Study - Lipner, Minna; Armon-Lotem, Sharon; Walters, Joel; Altman, Carmit (Frontiers in Psychology, 2021)
Introduction: Research in recent years has explored the vocabulary size (lexical breadth) of bilingual children, but less is known about the richness of bilingual word knowledge (lexical depth), and about how knowledge of words in the two languages interact. This study explores how bilingual narrative intervention with vocabulary instruction in each language may modulate crosslinguistic influence (CLI) between the languages of bilingual kindergarten children, focusing on CLI of lexical knowledge, and which factors modulate performance. Methods: Forty-one typically-developing English-Hebrew bilingual children (M = 64.63 months) participated. A bilingual adaptation of Story Champs narrative intervention program (Spencer & Petersen, 2012) was used to deliver vocabulary instruction in separate blocks of home language (HL) and school language (SL) sessions. Different intervention words were targeted in each language, but the children were tested on all target words in both languages. Lexical knowledge was assessed with a definition task four times throughout the study: prior to intervention, after each intervention block, and four-six weeks later. Learner characteristics (chronological age, age of onset of bilingualism and length of exposure) and proficiency in each language (standardized tests, familiarity with the vocabulary introduced in the intervention at baseline) were examined as possible modulators of performance. Results: Children showed growth in lexical breadth and depth in their HL/English after HL intervention and in lexical breadth in the SL/Hebrew following SL intervention, with CLI for semantic depth observed via a qualitative analysis, but not quantitatively. Better HL/English performance was correlated with later AoB (and shorter SL exposure) and higher HL language proficiency scores. Children with higher HL/English proficiency responded better to the SL/Hebrew intervention, gaining more than those with lower English proficiency. Children with SL/Hebrew vocabulary dominance at the outset of the study also gained more from the HL/English intervention. No correlations were found between learner characteristics and SL performance. Discussion: The current study indicates that bilingual narrative intervention with vocabulary instruction may be efficacious for improving the lexical breadth and depth of bilingual kindergarten children. It suggests that CLI may enhance bilingual children’s language learning success, and points to the importance of strengthening both languages of bilingual children.